(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines the history of the Kokand Khanate within the geopolitical dynamics of the 18th and 19th centuries. It analyzes the khanate’s origins, internal political structure, foreign relations with neighboring states, and the factors that led to its downfall and incorporation into the Russian Empire. Particular attention is paid to the Khanate’s relations with the Emirate of Bukhara, the Qing Dynasty of China, and Russia.